Mejores Prácticas de Manejo en el Area Agrícola de los Everglades: Prevención de el Derramamiento de Fertilizantes - Orlando A. Diaz; Samira H. Daroub; Ronald W. Rice; Timothy A. Lang; Viviana M. Nadal; Ming Chen (EDIS)
SL-231-Sp, a 3-page illustrated fact sheet by O.A. Diaz, S.H. Daroub, R.W. Rice, T.A. Lang, V.M. Nadal, and M. Chen, is the Spanish language version of SL-231, "Best Management Practices in the Everglades Agricultural Area: Fertilizer Spill Prevention." It provides current implementation guidelines for this BMP designed to reduce drainage P loads in the Everglades Agricultural Area (EAA). Includes references. Published by the UF Department of Soil and Water Sciences, May 2007.